The Role of the XBRL International Consortium in Digital Reporting Regulation - D. V. Spitsina (Учёт. Анализ. Аудит)
The last years of our century are marked by the beginning of a wide and active use of the open standard of business information exchange XBRL (eXtensible Business Reporting Language) in the world communication practice. Since this format is recognized by economists and information technology practitioners as a flexible reporting tool for integrating financial and non-financial information in accordance with the stakeholders’ needs, the format is evolving and spreading due to the activities of the XBRL International consortium. The aim of the study is to identify the key stages in the reporting transformation in line with the transition from prioritising the form of information presentation to the dominance of the content aspect. The scientific cognition and special methods of research were used in the paper, namely deduction, induction, comparison, analysis synthesis and graphical methods. The study determines the role of the XBRL International consortium in promoting a new reporting format in cooperation with regulatory authorities and business community representatives. XBRL format possibilities for both automating reporting and internal controls documentation are revealed. The definition of XBRL consulting is proposed. The study might be useful to the specialists engaged in the analysis of consulting service market and new technologies in accounting and reporting.